Fluvial deposition during transition from flexural to dynamic subsidence in the Cordilleran foreland basin: Ericson Formation, Western Wyoming, USA. (19th August 2014) - Leary, Ryan; DeCelles, Peter; Gehrels, George; Morriss, Matthew
Abstract The Ericson Formation was deposited in the distal foredeep of the Cordilleran foreland basin during Campanian time. Isopach data show that it records early dynamic subsidence and the onset of basin partitioning by Laramide uplifts. The Ericson Formation is well exposed around the Rock Springs uplift, a Laramide structural dome in southwestern Wyoming; the formation is thin, regionally extensive, and does not display the wedge‐shaped geometry typical of foredeep deposits. Sedimentation in this area was controlled both by activity in the thrust belt and by intraforeland tectonics. The Ericson Formation is ideally situated both spatially and temporally to study the transition from Sevier to Laramide (thin‐ to thick‐skinned) deformation which corresponded to the shift from flexural to dynamic subsidence and the demise of the Cretaceous foreland basin system. We establish the depositional age of the Ericson Formation as ca. 74 Ma through detrital zircon U–Pb analysis. Palaeocurrent data show a generally southeastward transport direction, but northward indicators near Flaming Gorge Reservoir suggest that the intraforeland Uinta uplift was rising and shedding sediment northward by late Campanian time. Petrographic data and detrital zircon U–Pb ages indicate that Ericson sediment was derived from erosion of Proterozoic quartzites and Palaeozoic and Mesozoic quartzose sandstones in the Sevier thrust belt to the west. The new data place temporal and geographic constraints on attempts to produce geodynamic models linking flat‐slab subduction of the oceanic Farallon plate to the onset of the Laramide orogenic event.